Aripiprazole salts. III. Bis(aripiprazolium) oxalate-oxalic acid (1/1) - Freire Espeleta, Eleonora (2013)
The asymmetric unit of the title salt [systematic name: bis(4-(2,3-dichlorophenyl)-1-{4-[(2-oxo-1,2,3,4-tetrahydroquinolin-7-yl)oxy] butyl}piperazin-1-ium) oxalate-oxalic acid (1/1)], 2C23H28Cl2N3O2 +·C2O4 2-·C2H2O4, consists of one protonated aripiprazole unit (HArip+), half an oxalate dianion and half an oxalic acid molecule, the latter two lying on inversion centres. The conformation of the HArip+ cation differs from that in other reported salts and resembles more the conformation of neutral Arip units in reported polymorphs and solvates. The intermolecular interaction linking HArip + cations is also similar to those in reported Arip compounds crystallizing in the space group P , with head-to-head N - H ⋯O hydrogen bonds generating centrosymmetric dimers, which are further organized into planar ribbons parallel to (01 ). The oxalate anions and oxalic acid molecules form hydrogen-bonded chains running along [010], which 'pierce' the planar ribbons, interacting with them through a number of stronger N - H ⋯O and weaker C - H ⋯O hydrogen bonds, forming a three-dimensional network.